Catalytic properties of the homologous series of the β-brominated-pyrrole manganese(III) tetraphenylporphyrins. (28th January 2016) - Rayati, Saeed; Nejabat, Fatemeh
Graphical abstract: A homologous series of β-brominated porphyrins (MnTPPBr x (OAc) ( x  = 0, 2, 4, 6 and 8)) was prepared and their catalytic properties in oxidation of cyclooctene were investigated as cytochrome P450 models, where the best results are achieved with the tetrabrominated complex. Abstract: A homologous series of β-brominated Mn-porphyrins were prepared and their catalytic activities were investigated in the oxidation of cyclooctene with urea hydrogen peroxide (UHP). The highest conversion of cyclooctene with UHP in ethanol was obtained in the presence of β-tetra-brominated meso -tetraphenylporphyrinatomanganese(III) acetate (MnTPPBr4 (OAc)). Therefore MnTPPBr4 (OAc) has been selected for oxidation of different alkenes and alkanes. In order to achieve maximum conversion, the effect of different parameters such as solvent, temperature, amount of oxidant, acetic acid as oxidant activator and also the amount of axial base as co-catalyst were investigated.